2013
DOI: 10.1039/c2bm00066k
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide nanoparticle-entrapped polyion complex micelles generate singlet oxygen in the cells by ultrasound irradiation for sonodynamic therapy

Abstract: A new modality of using ultrasound irradiation instead of photoactivation, as in photodynamic therapy (PDT), sonodynamic therapy, has emerged as a promising treatment for various types of cancer. Titanium dioxide (TiO 2 ) has the ability to generate reactive oxygen species (ROS) by not only photo-but also ultrasound-irradiation. Here, the formation of core-shell type polyion complex micelles from TiO 2 nanoparticles with polyallylamine bearing poly(ethylene glycol) grafts effectively improves the dispersion st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 40 publications
0
65
0
1
Order By: Relevance
“…Benefiting from the advances in PDT and photocatalysis, various inorganic photocatalysts have been demonstrated to be responsive to US exposure for generating ROS in an aqueous environment. Since the recent demonstration of US‐triggered ROS‐generating capability of TiO 2 nanoparticles, extensive efforts have been invested to explore the application potential of TiO 2 in SDT for improved antitumor efficacy. You et al have demonstrated that hydrophilized TiO 2 is effective to inhibit tumor growth after US treatment, accompanied by the upregulation of proinflammatory cytokines and interleukins (Figure b) .…”
Section: Nanocatalytic Medicine For Cancer Therapiesmentioning
confidence: 99%
“…Benefiting from the advances in PDT and photocatalysis, various inorganic photocatalysts have been demonstrated to be responsive to US exposure for generating ROS in an aqueous environment. Since the recent demonstration of US‐triggered ROS‐generating capability of TiO 2 nanoparticles, extensive efforts have been invested to explore the application potential of TiO 2 in SDT for improved antitumor efficacy. You et al have demonstrated that hydrophilized TiO 2 is effective to inhibit tumor growth after US treatment, accompanied by the upregulation of proinflammatory cytokines and interleukins (Figure b) .…”
Section: Nanocatalytic Medicine For Cancer Therapiesmentioning
confidence: 99%
“…TiO 2 ‐based polyion complex micelles were synthesized by using polyallyamine bearing poly(ethylene glycol) grafts (PAA‐g‐PEG) to encapsulate TiO 2 NPs ( Figure a) . Micelle coating on the surface of TiO 2 NPs realized the excellent dispersity of TiO 2 NPs, guaranteeing their further biomedical applications.…”
Section: Inorganic Micro/nanoparticle‐augmented Sonosensitizermentioning
confidence: 99%
“…Two types of PAA-g-PEGs having the same PAA main chain (degree of polymerization = 160) and bearing PEGs of different molecular weights (M n = 2000 and 550) and similar grafting densities (23 mol % for PEG2000 and 22 mol % for PEG550) were synthesized according to our previous report. 12 The chemical structure of PAA-g-PEG is shown in the Supporting Information ( Figure S1). The anatase TiO 2 NP dispersion (10 nm, pH <3) was purchased from Ishihara Sangyo Kaisha, Ltd. Fluorescent dyes, fluorescein, sulforhodamine B, and calcein were purchased from Wako Pure Chemical Industries, Sigma-Aldrich, and Tokyo Chemical Industries, respectively.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…4 We have recently reported the successful preparation of PIC micelles using titanium dioxide nanoparticles (TiO 2 NPs) and polyallylamine bearing poly(ethylene glycol) grafts (PAA-g-PEG) for application in sonodynamic therapy. 12 TiO 2 has the ability to act as both a photosensitizer and a sonosensitizer. Upon exposure to ultraviolet irradiation (UV, less than 390 nm) or ultrasound irradiation, it generates reactive oxygen species, including OH and HO 2 radicals, superoxide anions (O 2 − ), hydrogen peroxide (H 2 O 2 ), and singlet oxygen ( 1 O 2 ).…”
Section: ■ Introductionmentioning
confidence: 99%